Reversible reaction kinetic of tetraester formation simulation from secondary data: effect of temperature: article / Fatin Nabila Mohd Aripin - Mohd Aripin, Fatin Nabila (2019)
Renewable resources such as animal fats and plant oils can produced bio-lubricants that also known as oilbased lubricants whereas this product are environmentally friendly, biodegradable and non-toxic lubricants. A kinetic model that describe chemical transesterification of palm oilbased methyl esters (POMEs) with pentaerythritol (PE) has been developed. The kinetics of the transesterification reaction was modeled as four distinct elementary reversible seriesparallel reaction mechanisms is simplified to the overall equation. The model considers the transesterification reaction to take place in both forward and reverse directions. The resulting kinetics equations were solved using ode45 solver function in MATLAB, where the rate constants of the proposed kinetic model were determined by minimization of errors based on the optimum criteria of statistical analysis and by comparing the component concentrations at maximum and at equilibrium. The optimum temperature at 170°C. The validity of the model was tested by comparing the observed experimental values with the theoretical calculated data. A good correlation between simulated results and experimental data was observed, confirming that the model was able to predict the rate constants with plausible accuracy.